Beyond Networks and Relations: Towards Rethinking Creative Cluster Theory - Kong, Lily (Institutional Knowledge at Singapore Management University, 2009)
The concept of “creative clusters” is a difficult one, complicated not least by the complexity of its constituent components — the concept of “creativity” and the idea of “clusters”. The debates surrounding the explanatory value and the promise and potential of creative clusters are particularly significant in the face of the sometimes hypnotic hold of cluster creation on policy makers. Yet, scholars have observed that the heightened popularity of the cluster concept may mask its weak conceptual and empirical basis (Martin and Sunley 2003; Simmie 2004). In this chapter, I will examine the nature of creative clusters, and particularly, “cultural creative clusters” — i.e. clusters in which creative activity take place in the cultural field. This analysis is undertaken through detailed study of a specific visual arts cluster in Singapore and seeks to contribute to the development of a more nuanced theoretical position about the nature of creative clusters.